Topical bioavailability of diclofenac from locally-acting, dermatological formulations - Cordery, S.F.; Pensado, A.; Chiu, W.S.; Shehab, M.Z.; Bunge, A.L.; Delgado-Charro, M.B.; Guy, R.H. (International journal of pharmaceutics, 2017)
[Display omitted] Assessment of the bioavailability of topically applied drugs designed to act within or beneath the skin is a challenging objective. A number of different, but potentially complementary, techniques are under evaluation. The objective of this work was to evaluate in vitro skin penetration and stratum corneum tape-stripping in vivo as tools with which to measure topical diclofenac bioavailability from three approved and commercialized products (two gels and one solution). Drug uptake into, and its subsequent clearance from, the stratum corneum of human volunteers was used to estimate the input rate of diclofenac into the viable skin layers. This flux was compared to that measured across excised porcine skin in conventional diffusion cells. Both techniques clearly demonstrated (a) the superiority in terms of drug delivery from the solution, and (b) that the two gels performed similarly. There was qualitative and, importantly, quantitative agreement between the in vitro and in vivo measurements of drug flux into and beyond the viable skin. Evidence is therefore presented to support an in vivo − in vitro correlation between methods to assess topical drug bioavailability. The potential value of the stratum corneum tape-stripping technique to quantify drug delivery into (epi)dermal and subcutaneous tissue beneath the barrier is demonstrated.